2004
DOI: 10.2337/diabetes.53.9.2291
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of Multiple Hemostatic Abnormalities in Uremic Type 1 Diabetic Patients After Kidney-Pancreas Transplantation

Abstract: To evaluate the effects of kidney-pancreas transplantation on hemostatic abnormalities in uremic type 1 diabetic patients, we conducted a cross-sectional study involving 12 type 1 diabetic patients, 30 uremic type 1 diabetic patients, 27 uremic type 1 diabetic patients who had a kidney-pancreas transplant, 12 uremic type 1 diabetic patients who had a kidney-alone transplant, and 13 healthy control subjects. We evaluated platelet and clotting system. Platelets in the group of uremic type 1 diabetic patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Our group demonstrated that restoration of normoglycemia with kidney-pancreas transplantation has a large effect on hemostasis; therefore, some effect in islet-transplanted patients was expected as well (Table 1) [68]. Preliminary and unpublished data from our group confirmed that ITA patients, bearing a functioning graft, showed a better morphology of platelets, lower resting platelet calcium and CD41 expression (meaning less activated platelets), and reduced levels of prothrombotic factors compared with T1D patients on the waiting list (Table 1) …”
Section: Effects On Cardiovascular Complicationsmentioning
confidence: 84%
“…Our group demonstrated that restoration of normoglycemia with kidney-pancreas transplantation has a large effect on hemostasis; therefore, some effect in islet-transplanted patients was expected as well (Table 1) [68]. Preliminary and unpublished data from our group confirmed that ITA patients, bearing a functioning graft, showed a better morphology of platelets, lower resting platelet calcium and CD41 expression (meaning less activated platelets), and reduced levels of prothrombotic factors compared with T1D patients on the waiting list (Table 1) …”
Section: Effects On Cardiovascular Complicationsmentioning
confidence: 84%
“…The gold standard treatment for long-standing T1D is SPK, which affords stable glycometabolic control, near-normalize risk factors and prolonged survival (Table S4)(Fiorina et al, 2004; Fiorina et al, 2005; Folli et al, 2010; Secchi et al, 1998; Smets et al, 1999). However, individuals with T1D+ESRD are also treated with kidney transplantation alone but remain diabetic (K+T1D)(Fiorina et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…While it is clear that intensive glucose control results in reduction in both microvascular and macrovascular complications in T1DM, (19,20), the impact of pancreas transplantation on complications of diabetes, including nephropathy, retinopathy, and neuropathy, is more subtle (1,7,8). One potential explanation is that stabilization of diabetes control may lead to a reduction in cardiac events, a hypothesis supported by others (21)(22)(23)(24)(25). However, since 5-yr pancreas graft survival following SPK is only 71% (12), explanations other than euglycemia must be considered to account for the improved outcomes.…”
Section: Discussionmentioning
confidence: 97%